Materiality, Technology and the Subject: Elements of Critical Communication and Media Analysis - Gentzel, Peter (The Forgotten Subject. Subject Constitutions in Mediatized Everyday Worlds., 2023)
The article shows that the conceptions of subjectivity and materiality mutually refer to each other, but that this is neither adequately taken into account in traditional communication and media research nor in the discussion of practice theories, science and technology studies (STS) and actor-network theories (ANT). First, some basic assumptions of traditional communication analyses are discussed, which are said to be based on a psychologically truncated understanding of subjects and, at best, an undifferentiated treatment of media objects or media materiality. Theories of practice are also criticized for their bias towards reproduction and order, as well as for their deficient concept of the subject. With the help of STS and ANT, analytical models and findings on the meaning of media objects and materiality are also presented. Finally, with the help of Martin Heidegger’s technology analyses, a path for the critical adaptation of practice and material turn for communication and media analyses is outlined.<br
Keywords: Critical communication studies; Mediatization; Practice theory; Science and technology studies; Sociology of technology